La evolución en la comprensión del Pentateuco. Relevancia bíblica y teológica - García López, Félix (Estudios eclesiásticos, 2010)
After a brief introduction, this article points to four aspects related to the evolution / revolution in the understanding of the Pentateuch: first, the radical transformation in the classical historical-critical studies; second, an analysis of some of the main changes in modern historical-critical exegesis; third, the question for the biblical and theological relevance of such changes concerning historicity of the texts and biblical faith, uniqueness of ancient Israel and early Judaism, the divine project for humankind and Israel, and the meaning of the open end of Torah; fourth, pluralism of biblical readings typical of postmodernism.